Teaching English through songs (Journal of Pedagogical Inventions and Practices, 2021)
Globalization has a huge impact on the use of English in business, education, IT and any other field. English has become a lingua franca that chooses to communicate with those who speak another language. English has spread all over the world and this phenomenon has led to the study of English at an early stage in many countries where English is not spoken.